2012
DOI: 10.1002/cne.22761
|View full text |Cite
|
Sign up to set email alerts
|

Neuron numbers in the hypothalamus of the normal aging rhesus monkey: Stability across the adult lifespan and between the sexes

Abstract: Normal aging is accompanied by changes in hypothalamic functions including autonomic and endocrine functions and circadian rhythms. The rhesus monkey provides an excellent model of normal aging without the potential confounds of incipient Alzheimer's disease inherent in human populations. This study examined the hypothalamus of 51 rhesus monkeys (23 male, 18 female, 6.5–31 years old) using design-based stereology to obtain unbiased estimates of neuron and glia numbers and the Cavalieri method to estimate volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 78 publications
4
33
1
Order By: Relevance
“…There were also few effects of long‐term E 2 on ERα and PR cell % or density. Additionally, there were no changes in the total number of cells in either region, which is consistent with findings in other populations of macaques (Roberts et al, ). Differences between our model and published data using shorter‐term E 2 treatment suggest that changes previously observed in aged animals in the expression of ERα caused by HRT may be relatively transient, and that the nonhuman primate brain eventually returns to the pre‐treatment baseline.…”
Section: Implications and Conclusionsupporting
confidence: 91%
“…There were also few effects of long‐term E 2 on ERα and PR cell % or density. Additionally, there were no changes in the total number of cells in either region, which is consistent with findings in other populations of macaques (Roberts et al, ). Differences between our model and published data using shorter‐term E 2 treatment suggest that changes previously observed in aged animals in the expression of ERα caused by HRT may be relatively transient, and that the nonhuman primate brain eventually returns to the pre‐treatment baseline.…”
Section: Implications and Conclusionsupporting
confidence: 91%
“…Previous reports have found similarly robust rhythms of per gene expression in the SCN of young and old animals (Yamazaki et al, 2002; Davidson et al, 2008; Nakamura et al, 2011) although age-related changes in other clock genes have been reported (Kolker et al, 2003; Wyse and Coogan, 2010). Aging does not appear to reduce the overall number of SCN neurons (Madeira et al, 1995; Roberts et al, 2012), but alters specific SCN subpopulations and network properties (Roozendaal et al, 1987; Van der Zee et al, 1999; Duncan et al, 2001; Kallo et al, 2004; Palomba et al, 2008). Functional and organizational changes under steady-state entrainment conditions may have adverse consequences for physiological processes regulated by the circadian system and could contribute to functional deterioration associated with aging (Kondratova and Kondratov, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Since BDNF is normally expressed in both neurons and glial cells, especially astrocytes and microglia (Elkabes et al 1996;Wu et al 2004), the exact source of the decreased expression is unknown. However, as the rhesus monkey does not develop Alzheimer's disease (Sloane et al 1997) and does not lose forebrain neurons (Roberts et al 2012;Giannaris and Rosene 2012), this study shows that there is a decrease in the level of BDNF mRNA and proBDNF protein in the absence of the neuron loss that occurs in AD and other neurodegenerative diseases.…”
Section: Bdnf and Normal Agingmentioning
confidence: 67%